Self-reports and peer-ratings of shyness and assertiveness - Zarevski, Predrag (Array, 2002)
High school students (N=336 ; 67% females) were asked to assess themselves and their peers on questionnaire measuring shyness and assertiveness (Zarevski & Vukosav, 1997). Factor analysis clearly differentiates self-reports on these constructs. Peer-ratings show less clear differentiation between shyness and assertiveness and presence of a strong halo-effect. Namely, the ratio between 1st and 2nd Eigen value extracted from correlation matrix with items measuring shyness and assertiveness is much greater for peer-ratings than for self-reports (in female sample variances explained by first two principal components for peer reports were 23% : 6% and for self-reports 14% : 10% for males respective values were 27% : 7% and 14% : 7%). The strong halo-effect in peer-ratings is also reflected in high internal homogeneity. Correlations between self-ratings and peer-ratings are higher for shyness (rfemale=.37, rmale =.35) than assertiveness (rfemale =.31, rmale = .20). It remains unclear wheather is this primarily the result of better psychometric qualities of shyness scale or the fact that it might be easier to observe shyness more accurately than assertiveness.